Chapter 4 Digital Twins in Smart Manufacturing - Aziz, Shahid (Taylor & Francis, 2024)
A digital twin is a digital replica of a living or non-living physical entity, such as a manufacturing process, medical device, piece of medical equipment, and even a person to gain insight into the present and future operational states of each physical twin." With the rapid advancement in manufacturing processes through sensors, the Internet of Things (IoT), modeling software, cloud computing, and cyber-physical integration, smart manufacturing is being adopted by almost all manufacturers. Digital twin promises the realization of smart manufacturing through the interaction and utilization of all these technological advances. Therefore, it is necessary to educate the industrialists and researchers involved in the manufacturing industry on the recent progress and directions of digital twin technology and services. In general, this work introduces the digital twin technology and presents case studies specifically for smart manufacturing from the perspective of industry 4.0. It also presents the digital twin for smart product design, biomanufacturing, and IoT with case studies. It gives its readers a guideline for future trends and an application framework for product design using digital twins.